Research Gap Of E-Hrm: A Systematic Review - Harry Harry; Iryani Iryani (Program Pascasarjana STIE Amkop Makassar, 2022)
The aim of this study to identify five research questions: (RQ1) the trend of E-HRM publications in the Google Scholar database in 2000-2023; (RQ2) publishers that published the most E-HRM articles; (RQ3) active researcher; (RQ4) most cited article titles; and (RQ5) publication network map. The research method uses a systematic review. The data is sourced from the Google Scholar database which is limited in terms of: (1) the type of bibliography used; and (2) keywords used